Analysis Of Core Supply Chain Process Performance Based On The Lean Six Sigma Supply Chain Management Approach (Case Study: PT Pg. Candi Baru) - Krisna Ramadhian Arifano; Dira Ernawati; Sinta Dewi (Eduvest - Journal of Universal Studies, 2024)
The aim of the research is to integrate the lean six sigma supply chain management concept to design and measure performance measurement models and determine the causes of company performance failures and then provide recommendations for improvement according to the lean concept. This research was carried out only up to the improvement stage. The result of this research is an overall performance measurement of 66.6666 where this value can be categorized as "Average". This value shows that supply chain management activities at PT. PG Candi Baru is running moderately and obtained 9 KPIs that have not reached the target. Waste is the cause of the 9 KPIs not achieving the target, namely waste defects, waiting, not utilizing employee knowledge, skills and abilities and extra processing. Recommendations for improvement given to the company to reduce the occurrence of waste are: For defects in sugar quality, the proposed improvement is to carry out milling in accordance with established standards and use raw materials that comply with specifications. When waiting for raw materials to be late, the proposed improvement is that the plant department must carry out earlier purchasing planning to avoid waste waiting and prioritize TS suppliers because they have a higher weight than other suppliers. The proposed improvement for the production department is training on how to forecast production scheduling. In extra processing, the proposed improvement is that the company can provide a quality control list when inspecting the finished product so that the inspection is more controlled.